New and convenient route for the synthesis of some new pyrazol-5-yl-1h-imidazole derivatives - Zonouzi, A.; Mirzazadeh, R.; Talebi, M.; Jafarypoor, R.; Peivandi, A.; Ng, S.W. (Elsevier, 2010)
A simple and efficient method for the synthesis of some new pyrazol-5-yl-1H-imidazoles 4a-h is described. In this method oxazolones 5a-h were produced as minor products. The X-ray analysis confirmed the structures of 4 and 5.